ANALISIS POTENSI PENGEMBANGAN KOMODITAS JAGUNG DI WILAYAH PERBATASAN NKRI – PNG KABUPATEN KEEROM PAPUA - Beding, Petrus Alexander; Lewaherilla, Niki E.; Lestari, Rohimah H.; Tirajoh, Siska (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
Corn is a strategic agricultural commodity that has a role as food material, raw material for the food and feed industry. The analysis of the corn commodity development in Keerom district aims to identify the district/sub-district as the base area for superior commodities, evaluate the area of land for corn development, and the feasibility analysis of corn farming in Keerom district was carried out in January - December 2018, with primary and secondary data approaches. Primary data through surveys and interviews with respondents using a questionnaire on characteristics, land tenure, production and productivity, costs and income. Secondary data through literature studies such as harvest area, production and productivity, was obtained from BPS Keerom and the Department of Agriculture and Fisheries of Keerom Regency in 2014-2018. Determination of the District area as the basis for developing corn commodities as a superior commodity using Location Quotient (LQ) analysis with the criteria of LQ value> 1, so that corn commodity is the base commodity or as a superior commodity in the District. Farming feasibility analysis based on costs and benefits in the form; R / C ratio, business efficiency. The results of the analysis of corn commodity development bases in Keerom district are Web, Yaffi, Arso, Towe, Arso Barat, and Arso Timur Districts. The area of land suitable for maize development in Keerom district is 294,209 ha, very suitable land (S1) 78,077 ha (8.60%); Sufficiently suitable land (S2) covering an area of 164,036 ha (18.08%). Based on the results of the feasibility analysis of corn farming using PTT technology innovation, it is feasible to be developed (R/C> 1) with a business efficiency of 35.31%.